Societies in Eclipse : Archaeology of the Eastern Woodlands Indians, A.D. 1400-1700. - Brose, David S. (University of Alabama Press, 2010)
While contact with explorers, missionaries, and traders made a significant impact on natives of the Eastern Woodlands, Indian peoples cannot be solely understood from the historical record. Here, in Societies in Eclipse, archaeologists combine recent research with insights from anthropology, historiography, and oral tradition to examine the cultural landscape preceding and immediately following the arrival of Europeans. The evidence suggests that native societies were in the process of significant cultural transformation prior to contact.